Health professionals’ implicit attitudes towards dementia - Staniec, Rachael (2019)
Background: The quality of dementia care has been shown to be positively associated with the attitudes of staff providing care. Research to date has involved explicit attitudes, which has identified negative, neutral and positive biases amongst staff working with those with dementia. Whilst explicit attitudes have been outlined as informing deliberate processes, implicit attitudes have been argued to inform spontaneous behaviours, ranging from facial reactions to judgements on care. Implicit attitudes are argued to inform behaviour when there is insufficient motivation, opportunity and cognitive capacity to deliberate upon information. Within busy care environments staff may have limited cognitive capacity, which may lead to more instances of implicit attitudes informing behaviour. There have been no studies to date investigating implicit attitudes towards dementia. The study investigated the following objectives; (1) whether there was evidence of implicit bias in professional responses to individuals with dementia; (2) to ascertain whether implicit attitudes diverge from explicit attitudes; and (3) to test whether attitudes are sensitive to the amount of professional experience with individuals who have dementia.